Configuraciones causales de la alta tasa del delito de robo a transeúntes en la Zona Metropolitana del Valle de México (2021)
The article aims to identify the causal configurations of the high rate of pedestrian robbery in the districts of the Metropolitan Area of the Valley of Mexico (ZMVM). Based on the theories of social disorganization and routine activities, the hypothesis is that this phenomenon occurs in contexts where conditions associated with the presence of potential offenders and criminal opportunities are combined. The methodology is based on a comparative qualitative analysis using the fuzzy set technique (fsQCA). The hypothesis is empirically tested, and shows the causal complexity of the spatial concentration of crime in terms of equifinality, although the theoretical projections showed contextual limits.